Immunohistochemical expression of BerEP4, CK7 and EMA in basal cell carcinoma of the skin - Bartoš, Vladimír (Bangabandhu Sheikh Mujib Medical University Journal, 2019)
The aim of this study was to evaluate the immunohistochemical expression status of BerEP4, EMA and CK7 in cutaneous basal cell carcinoma (BCC) and to find out whether there is some difference in the expression pattern related to the anatomic location of lesions. Biopsy specimens from 32 cases of BCC of the skin were enrolled. All samples were immunohistochemically stained for EpCAM (clone BerEP4), EMA (clone E29), and CK7 (clone OV-TL 12/30). All cases (32/32; 100%) were strongly positive for BerEP4, while the vast majority of tumors (28/32) were completely negative for EMA. Four BCCs (12.5%) exhibited a focal staining for EMA, but it was only sporadic and did not exceed 5% of tumor epithelium. Cytoplasmic expression of CK7 was found in 19 cases (19/32; 59.4%). Comparing both, the chronically sun-exposed and the intermittently sun-exposed anatomic locations, the percentages of CK7-positive BCCs were 47.8 and 88.9%, respectively. In conclusion, all lesions showed a strong expression of BerEP4, the use of this marker is helpful especially in individuals suspected of having multifocal BCC with many microlesions, morpheic BCC, or BCCs with mixed histomorphology.